Gis Applications Using Location Based Service (LBS) Methods Based On Android. (A Case Study In Bandar Lampung) - Thamrin T; Susanty W; Astari I N (Bandar Lampung University (UBL), 2017)
Bandar Lampung city is one of the cities in Lampung Province and is the capital city of Lampung Province. In Bandar Lampung city, there are still locations such as tourist objects, hospitals, hotels / inns, education (high schools/ vocational schools / university), restaurants, and malls / traditional markets that have not beeb explored so that many local and non-local tourists do not know the location. Thus, the author designed an android-based application that is the profile of Bandar Lampung city (Probal) which aims to help or facilitate the people of Bandar Lampung city and tourists who come from various regions to simplify finding the locations in of Bandar Lampung city by using location based service (LBS) method.